Challenges in nursing continuing education: A qualitative study - Jalil Eslamian; Mahin Moeini; Marzie Soleimani (Wolters Kluwer Medknow Publications, 2015)
Background: Nursing continuing education with development of knowledge, skill, and attitude results in improvement of nursing activity, and thus improves the health care in the society. If the education is not planned and implement properly, it affects the patient care. This study was designed to explore the challenges of nursing continuing education in Isfahan University of Medical Sciences hospitals. Materials and Methods: The research was conducted from April 2012 to February 2013 in Isfahan, Iran. The sampling was begun with purposeful method and continued with snowball method. Thirty-nine participants were selected among the nurses of Alzahra, Kashani, and Noor hospitals, nursing and midwifery faculty, continuing education center, and the vice-chancellery for treatment. The participants were both learners and planners of continuing education program. In this descriptive explorative qualitative research, we interviewed 39 participants in five focus group and five individual interviews, until data saturation was achieved. We used semi-structured interviews and field notes for data gathering, and members checking, triangulation (data and method), peer debriefing, and peer review to increase the strength of data. Data were analyzed with thematic analysis method that was proposed by Broun and Clarke in 2006. Results: Data analysis produced 175 initial codes, 8 subthemes, and 5 main themes. The main themes included: Learners related factors, teachers related factors, educational process related factors, inadequate facilities, and defective evaluation. Conclusions: According to the results, we need to revise the educational process in nursing continuing education. To achieve this goal, we need a team for needs assessment, planning, and evaluation. In addition, we must pay attention to educators' and learners' issues.